KARYA-KARYA HABIB USMAN BIN YAHYA: RELEVANSI ADABUL INSAN DAN SIFAT DUA PULUH SEBAGAI PEDOMAN BERAGAMA MASYARAKAT BETAWI-JAKARTA - Mu'jizah; Purnama, muhammad Deden (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2024)
Betawi people – who live in Jakarta and its near-area–are known as Muslims. One of the many great Jakarta scholars who produced Islamic works that enriched the traditions of the Betawi-Jakarta people was Habib Usman bin Yahya, a prominent scholar from the late 19th to early 20th centuries. This research aims to explain the function and meaning of two of Habib Usman's works for the Betawi-Jakarta Islamic community, namely Adabul Insan and Sifat Dua Puluh. The method used in this research is qualitative. Data sources were obtained through internet articles, books, journals and interviews. The results of the research show that several of Habib Usman's works are still being studied by the Betawi-Jakarta community, for example Adabul Insan and Sifat Dua Puluh. The preservation of Habib Usman's works is carried out by studying them at taklim councils, for example in Pondok Bambu, East Jakarta– the location where Habib Usman is buried, which is organized by Habib Usman's female descendant family–the Banahsan clan–through recitations for teenagers to adults. Apart from that, Adabul Insan and Sifat Dua Puluh are also discussed at the Daarul Amaanah in West Jakarta through routine book studies every Thursday evening – taught by two clerics descended from the Bin Yahya family.